Proceedings of Latin American and Caribbean Petroleum Engineering Conference 1999
DOI: 10.2523/53789-ms
|View full text |Cite
|
Sign up to set email alerts
|

Sand Control in Open Hole Horizontal Wells-Case Histories and Developments

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractThe discovery of new fields in the Amazon forest and in deep water offshore Campos Basin, all of them consisted of unconsolidated sand, led Petrobras to adopt non conventional wells and sand control techniques. The main goals were to increase productivity, delay gas/water conning and support unconsolidated formations in water injection wells.The first horizontal well was completed in December 94 in Rio Urucu field. Since there was only one zone to drain the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…These wells, with laterals ranging from 850 to 1500 ft, have experienced PI's ranging from 36 bopd/psi to 80 bopd/psi, all of which exceed productivity estimates for similar wells in the field. In fact the well with the 80 bopd/psi productivity index, has been reported to be 3 times as productive as the average non-gravel packed horizontal in that field 7 .…”
Section: Effect Of Hole Cleaning Technique On Productivitymentioning
confidence: 61%
See 1 more Smart Citation
“…These wells, with laterals ranging from 850 to 1500 ft, have experienced PI's ranging from 36 bopd/psi to 80 bopd/psi, all of which exceed productivity estimates for similar wells in the field. In fact the well with the 80 bopd/psi productivity index, has been reported to be 3 times as productive as the average non-gravel packed horizontal in that field 7 .…”
Section: Effect Of Hole Cleaning Technique On Productivitymentioning
confidence: 61%
“…Set and test packer. 7. With the tool in the lower circulating position (i.e., with the workstring stabbed into the screen's circulating shoe to prevent fluid movement through the screen), the solids-free viscous pill is then displaced from the WWS/open hole annulus into the cased hole/workstring annulus using a volume of brine at least equal to the open hole and tail pipe volume.…”
Section: Hole Cleaning At East Wilmington Fieldmentioning
confidence: 99%
“…Despite the lower flow rate per foot of formation and consequently smaller flowing pressure drop than in a conventional well, numerical simulations showed that sand control is required, even in the horizontal injection wells 7,8 . Despite the lower flow rate per foot of formation and consequently smaller flowing pressure drop than in a conventional well, numerical simulations showed that sand control is required, even in the horizontal injection wells 7,8 .…”
Section: Sand Contention Mechanisms the Reservoirs In The Marlimmentioning
confidence: 97%